2011
DOI: 10.1038/ncomms1501
|View full text |Cite
|
Sign up to set email alerts
|

Control of electronic conduction at an oxide heterointerface using surface polar adsorbates

Abstract: The interface between LaAlo 3 and srTio 3 possesses a range of intriguing properties, notably a proposed connection between the surface state of the LaAlo 3 and the conductivity buried in the srTio 3 . Here we study the effect of the surface adsorption of a variety of common laboratory solvents on the conductivity at the interface between LaAlo 3 and srTio 3 . We show that the application of chemicals such as acetone, ethanol, and water can induce a large change in the conductivity, and, in particular, an insu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
137
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(143 citation statements)
references
References 33 publications
4
137
1
1
Order By: Relevance
“…3(j), very short voltage pulses on the Pt electrode in our device can set the device because the LAO layer is extremely thin and the oxygen vacancies only need to migrate across the LAO/ STO interface to accomplish the forming process, realizing the LRS. Besides the applied bias, the internal field within the LAO layer is a function of several factors, including the film thickness, electrode type, and even surface absorbates [16,[51][52][53][54][55][56][57]. This built-in field may contribute to the asymmetry of the energy barrier for the migration of oxygen vacancies [ Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3(j), very short voltage pulses on the Pt electrode in our device can set the device because the LAO layer is extremely thin and the oxygen vacancies only need to migrate across the LAO/ STO interface to accomplish the forming process, realizing the LRS. Besides the applied bias, the internal field within the LAO layer is a function of several factors, including the film thickness, electrode type, and even surface absorbates [16,[51][52][53][54][55][56][57]. This built-in field may contribute to the asymmetry of the energy barrier for the migration of oxygen vacancies [ Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Most experimental investigations have been performed with conducting interfaces, a regime for which higher-temperature ferromagnetism is suppressed. Any inhomogeneity that locally depletes the interface, for example, defects or surface adsorbates 24 , could give rise to local insulating regions that exhibit magnetic behaviour. Similarly, LAO/STO structures grown at pressures close to the insulating transition (for example, P(O 2 ) ¼ 10 À 2 mbar for ref.…”
Section: Discussionmentioning
confidence: 99%
“…The electron density at the interface can be controlled using a number of techniques including back-gating 22 , top-gating 23 , polar adsorbates 24 or via nanoscale control using conductive atomic force microscopy (AFM) lithography 25 .…”
mentioning
confidence: 99%
“…However, it is often difficult to achieve such high electric fields by conventional dielectric gates. 1,2 Recently, extra-high electric fields are achieved by approaches such as Schottky junctions, 3,4 polar adsorbates 5,6 or ionic liquids [7][8][9][10][11][12] as dielectric gates in field-effect transistor devices. 13,14 For example, Xu et al 15 studied the modulation of grain boundary barriers in ZnMgO/ZnO/sapphire heterostructure by DI water and they found that the electronic conduction property of ZnO layer far beneath the surface could be switched from Ohmic to Schottky junction.…”
Section: Introductionmentioning
confidence: 99%